Possible Anti-cardiovascular Boosting Properties of Sphenostylis stenocarpa Seed Oil and Milk on Salt Loading-induced Hypertension in Rats - Nwankwo Michael Olisa; Ogbonna Innocent Okonkwo; Yila Lakabra David (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
Legumes have been shown to have strong nutraceutical potentials, and this made them the strong source of nutrients that protect the human health. Protection of the heart from malfunctioning is a sure way of averting the incidence of cardiovascular diseases (CVDs), which have been one of the major causes of death in middle and high income countries. Out of the 17 million premature deaths (under the age of 70) due to non-communicable diseases in 2015, 82% are in middle and high income countries, and 37% are caused by CVDs. The most preventive measure for cardiovascular disease is primary prevention of risk factors. Most cardiovascular diseases can be prevented by addressing behavioural risk factors such as tobacco use, unhealthy diet and obesity, physical inactivity and harmful use of alcohol using population-wide strategies. People with cardiovascular diseases or who are at high cardiovascular risk (due to the presence of one or more risk factors such as hypertension, diabetes, hyperlipidaemia or already established disease) need early detection and management using counselling and medicines, as appropriate. Sphenostylis stenocarpa (Hochst. ex. A. Rich) Harms is an orphan legume crop which its oil and milk when administered to hypertensive albino rats, significantly (p< 0.05) lowered the atherogenic index of plasma (AIP), which is a strong marker for predicting the risk of cardiovascular disease. Hypertension was induced in rats using saturated NaCl solution. The rats were treated with the extracted oil and milk at different concentrations. It was observed that Sphenostylis stenocarpa seed has low glycaemic index and that at varying concentrations and time significantly (p < 0.05) lowered the AIP.